Compliments styles across gender in artists’ Instagram comments: A study of language and emoji usage - Insan, Raudatul Nurul; Agus Eko Cahyono (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Language serves a pivotal role in social interaction, including the performance of compliments as a key speech act for building rapport. This study conducts a sociolinguistic analysis of gendered differences in language style and emoji use within compliment exchanges on Instagram. Employing a descriptive qualitative methodology, the research utilizes a documentation approach to collect a corpus of 160 comments, evenly sampled from male and female users. These comments were extracted from ten Hollywood celebrity Instagram accounts (specifically, actors known for superhero film roles, each with over 10 million followers). Guided by Tannen’s (1990) Genderlect Style Theory, the analysis reveals significant gendered patterns. In same-gender interactions, men predominantly employ a “report talk” style, characterized by informative and referential language, whereas women favor “rapport talk,” which is more affiliative and collaborative. However, in cross-gender interactions, both genders demonstrate stylistic flexibility, utilizing a more balanced mix of report and rapport talk. Regarding paralinguistic features, male users show a greater tendency toward evaluative emojis, while female users more frequently employ expressive emojis. In terms of compliment topics, aligned with Holmes’s (1986) taxonomy, both men and women directed compliments across all major categories: appearance, ability/performance, possessions, and personality/friendship, indicating a shared thematic repertoire despite stylistic divergence.